Isotopic composition of Holocene shells from raised beaches and ice shelves at Terra Nova Bay (Northern Victoria Land, Antarctica). - BARONI, CARLO; STENNI B; LONGINELLI A. (1991)
Seventy-six samples of calcium carbonate from shells and skeletons of fossil marine. organisms collected in the area of Terra Nova Bay (Victoria Land, Antarctica) have been measured for their 13C/12C and 180 /160 ratios. Solitary corals have been measured along with bryozoans, cirripeds, serpulids and pelecypods coming from fossil beaches, supraglacial debris and dirt cones. Age determinations have been carried out by means of 14C measurements. The isotopic results obtained may be summarized as follows: the measurements carried out on corals agree well with previous measurements clearly indicating that these organisms do not precipitate the CaC03 of their skeleton under isotopic equilibrium conditions with environmental water. The 0 180 (COi-) are probably shifted by a constant value when compared with the 0180(~Oi-) values at equilibrium. The isotopic results obtained from bryozoans do not agree with the data reported in the literature. Our specimens show <S180 values away from isotopic equilibrium condition and <S13Cvalues very close to those of "normal" marine carbonate. Four different species of pelecypods have been studied, their age ranging from recent to about 7000 years B.P. In the case of Adamussium colbecki, there seems to be: a; relationship between age and 8180 (C0 32-), older specimens yielding more negative < 5 180 values. The isotopic values obtained from cirripeds suggest similar conclusions. Finally, both the oxygen and, carbon isotopic values of serpulids are not very far from equilibrium conditions. The main interest of these preliminary data is represented by the possibility of detecting relatively. small climatic changes even under these extreme conditions and by the possibility of obtaining information on the biological behaviour of various marine organisms living in this peculiar environment.